Mary Austin Holley : the Texas diary, 1835-1838 - Holley, Mary Austin, 1784-1846 (The University of Texas, 2014)
Mary Austin Holley (1784?1846), a cousin of Stephen F. Austin, journeyed to Texas on three separate occasions. Her first visit, in 1831, resulted in the publication of her book, Texas. Her second and third trips, in 1835 and 1837, were depicted in her diary. This witty, observant, and highly perceptive woman captured the infant Texas in her journal?the Mexican state moving toward rebellion and the new Republic, dynamic and struggling with a great destiny. The Holley diary is an important insight into the social and political history of early Texas.